The impact of teacher bonuses on student performance in full-time schools: The case of the Espírito Santo - Guedes, Heber Gonçalves; Beiruth, Aziz Xavier (Contextus - Revista Contemporânea de Economia e Gestão, 2021)
The goal of the study was to analyze the effect of granting financial incentives to teachers in relation to the performance of students from full-time schools of Espírito Santo. A method of matching was used by means PSM (propensity score matching) and then a Tobit regression to analyze the exam scores of the SAEB (National Basic Education Assessment System) in 2017. The results found showed that there is a positive association and related between the BD (Bonificação por Desempenho) program and the Portuguese and mathematics grades of third-year high school students from full-time schools in Espírito Santo. The work concludes by explaining that the success of the program to the reduction in absenteeism and the decrease in teacher turnover.